THE CONCEPT OF PSYCHOSPIRITUAL WELL-BEING FROM WESTERN AND ISLAMIC PERSPECTIVES: A CONCEPTUAL DISCUSSION - Shamsuddin, Fathiah; Yusof, Siti Nubailah Mohd.; Sukor, Nurhafizah Mohd. (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The global economy, technological advancements, and quality of life have led to a decline in general well-being and moral and spiritual values, resulting in increased self-destructive behaviours and psychological disorders. The psychospiritual approach, a recent innovation in psychology and therapy, aims to address these limitations by integrating psychological and spiritual dimensions to enhance spiritual well-being and positively influence overall well-being. This study employed qualitative document analysis to explore psychospiritual well-being from both Western and Islamic perspectives and identify components of Islamic psychospiritual well-being that can effectively address mental health issues. The findings indicate that Western psychospiritual frameworks have evolved from a dualistic approach of mind and body to a more comprehensive framework that integrates both psychological and spiritual dimensions. Spiritual well-being is characterized by introspective mystical experiences of the mind, body, and spirit, and the human potential for self-actualization and transcendence. In contrast, the Islamic framework emphasizes maintaining purity and faith through the process of "tazkiyatun an nafs," or the purification of the soul of mujāhadah al-nafs (the inner struggle of the soul), madhmūmmah (the cleansing of blameworthy traits), maḥmūdah (the cultivation of praiseworthy traits), and riyāḍah al-nafs (self-discipline), to achieve the revered state of the peaceful and contented soul, the nafs al-mutma’innah. This spiritual development is deeply rooted in the teachings of the Quran and Sunnah, with a particular focus on Imam al-Ghazali's four key components of psychospiritual well-being: God-consciousness, the Vision of Dunyā for Ākhirah, Others-centeredness, and Inner Change. They facilitate a gradual progression towards forging a meaningful connection with Allah SWT and the realisation of Ihsan, or excellence, in both earthly life and the Hereafter.